Menganalisis Potret Pertanian Indonesia Meliputi Tanaman Palawija, Perkebunan, Kehutanan Peternakan dan Perikanan - Bramantara, Ezar Nafis; Rokmah, Dhaful Oktaviatul; Yasin, Muhammad (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Agriculture is a very important sector for sustainability and food security in Indonesia. As a country that has extensive agricultural potential, Indonesia has an agricultural sector that covers various aspects such as secondary crops, plantations, animal husbandry, forestry and fisheries. Palawija is a crop that is often planted by farmers in Indonesia. In this paper the author aims to describe a portrait of agriculture in Indonesia along with actual issues related to agriculture. This research uses a descriptive qualitative research design. The main data in this research is library data, namely from written texts related to the theme of the writing. The research results show that the portrait of Indonesian agriculture covers several sectors, including secondary crops, agriculture, plantations, animal husbandry and forestry. The case study was chosen to gain a deeper understanding of the portrait of agriculture in the area, including secondary crops, plantations, animal husbandry, forestry and fisheries. The plantation sub-sector is the sub-sector that has the highest contribution to Indonesia's GDP in 2021, amounting to 3.94%. In development, the agricultural, forestry and fisheries sectors have an important role in the country's development. The subsectors that are the biggest contributors are annual plantations, food crops, animal husbandry and annual horticultural crops.